2021
DOI: 10.1002/eji.202048949
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and expansion of thymus‐derived regulatory T cells for use in pediatric heart transplant patients

Abstract: Regulatory T‐cells (Tregs) are a subset of T cells generated in the thymus with intrinsic immunosuppressive properties. Phase I clinical trials have shown safety and feasibility of Treg infusion to promote immune tolerance and new studies are ongoing to evaluate their efficacy. During heart transplantation, thymic tissue is routinely discarded providing an attractive source of Tregs. In this study, we developed a GMP‐compatible protocol for expanding sorted thymus‐derived CD3+CD4+CD25+CD127– (Tregs) as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Indeed, Dijke and collaborators ( 27 ) showed that a large amount of stable, long-lived and potent FOXP3 + Treg could be isolated and expanded from a single thymus. Furthermore, Romano and colleagues ( 28 ) have recently reported a good manufacturing practice (GMP) compliant protocol to isolate and expand thymus-derived Treg cells, confirming the feasibility of the strategy. This is a revolutionary approach since children with heart diseases requiring cardiac surgery often undergo thymectomy to clear the surgical field.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Indeed, Dijke and collaborators ( 27 ) showed that a large amount of stable, long-lived and potent FOXP3 + Treg could be isolated and expanded from a single thymus. Furthermore, Romano and colleagues ( 28 ) have recently reported a good manufacturing practice (GMP) compliant protocol to isolate and expand thymus-derived Treg cells, confirming the feasibility of the strategy. This is a revolutionary approach since children with heart diseases requiring cardiac surgery often undergo thymectomy to clear the surgical field.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, the search for an alternative source of Treg with a predominantly naïve state that allows obtaining enough quantity of cells is crucial to overcome the limitations encountered in peripheral blood and umbilical cord blood. In this sense, the thymus, a primary lymphoid organ responsible for the maturation and differentiation of T and Treg cells, which is located above the heart and discarded to gain access to the heart during pediatric cardiac surgeries, could be employed as a new source of highly undifferentiated Treg ( 27 , 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thymic tissue is routinely discarded during heart transplant, however it contains regulatory T-cells with intrinsic immunosuppressive properties which might promote tolerance in transplant recipients. 14,15 Similar opportunities to influence the donor's immune system might also exist by electively including splenic or lymphatic tissue at the time of heart transplant.…”
Section: Discussionmentioning
confidence: 99%
“…While it would clearly be unreasonable to contend that a patient should receive a vital organ if they do not need it, these findings do suggest that increased attention should be paid toward the potential benefits of including additional donor tissue at the time of heart transplant. Thymic tissue is routinely discarded during heart transplant, however it contains regulatory T‐cells with intrinsic immunosuppressive properties which might promote tolerance in transplant recipients 14,15 . Similar opportunities to influence the donor's immune system might also exist by electively including splenic or lymphatic tissue at the time of heart transplant.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that CD4, CD25 and FOXP3 are key Treg markers and are partially associated with their functional properties. Tregs can be isolated from the peripheral blood (PB) ( Landwehr-Kenzel et al, 2018 ; Roemhild et al, 2020 ), umbilical cord ( Brunstein et al, 2011 ; Brunstein et al, 2016 ), thymus ( Romano et al, 2021 ) or leukapheresis products ( Peters et al, 2008 ; Wiesinger et al, 2017 ; Mathew et al, 2018 ). Of the available options PB is the least invasive, well tolerated by the patient and routinely collected in the clinics.…”
Section: Manufacturing Of Human Regulatory T Cell Productsmentioning
confidence: 99%